Anther structure and pollen development in species of Rubiaceae and anatomical evidence of pathway to morphological dioecy - Judkevich, Marina Daniela (2022)
We conducted anatomical analysis of anthers with the aim to establish the differences in the development pattern of microsporophytes and microgametophytes between perfect and imperfect flowers in the tribe Gardenieae (Rubiaceae). The species studied were: Tocoyena formosa (monoecious with perfect flowers), Cordiera concolor, Genipa americana, Randia calycina, and Randia sp. (dioecious with imperfect flowers). Flowers in successive stages of development were collected and fixed. The material was processed and examined using light microscopy and scanning electron microscopy. The present study revealed the stage when pollen is arrested in the functionally pistillate flowers of the dioecious taxa. Based on these observations an evolutionary sequence of changes towards the reduction of non-functional anthers in Rubiaceae is proposed. In addition, we describe and discuss characters that might be of importance in future phylogenetic studies in Rubiaceae (e.g. pollen morphology and its dispersal unit, the presence of orbicules, and a new type of placentoid).